The effect of ageing on Arenga pinnata fibre reinforced epoxy composite - Sinin, Saifuliwan Ezzedin; Ali, Aidy; Sanuddin, Asmawi (2009)
The aim of this study is to determine the effect of ageing in Arenga Pinnata Fibre Reinforced Epoxy Composites (APFREC) by undergoing an accelerated ageing process. A hand layup process was used to produce the composites samples. Only 10% of long random fibre was used in the composite according to weight fraction. To characterize the mechanical properties of the aged composites, tensile test and impact tests were performed on as produced and aged APFREC. The tensile test is performed in accordance to ASTM D 5083-96 while for impact test is performed in accordance to ASTM D 256-00. The results of as produced and aged samples were compared to differentiate the effects of the composite after ageing. The results shows that aged specimens have higher tensile strength compared to as produced specimens by 50.4%. However for impact tests, aged specimens’ shows a slight 6.33% degradation in impact strength compared to as produced specimens. The results show that as the APFREC age, the composite show an increase of ductility but a significant decrease in strength.